Puzzling Clinical Appearance of a Pancreatic Tuberculosis Case - Anak Agung Fendy Tri Wicaksana; Bramantono Bramantono; Musofa Rusli; M Vitanata Arfijanto; Usman Hadi (Interna Publishing, 2023)
Tuberculosis (TB) is generally known as an infectious disease caused by Mycobacterium tuberculosis. Not only the lungs, TB can also infect various other organs. Pancreatic TB is a rare manifestation of extrapulmonary TB infection accounting for only 0-4.7% of the total TB cases worldwide. It's still intricating for clinicians to diagnose pancreatic TB due to the extremely rare prevalence and non-specific clinical signs and symptoms. Herein we report a 71-year-old male patient complaining of jaundice and weight loss. Clinical condition, laboratory and tumor markers, also MRI imaging showed no abnormality. We made the diagnosis through histopathological examination of tissues extracted from bypass biliodigestive procedure, showing granulomas, along with confirmed bacteriological analysis with Ziehl Nelsen staining. This patient received Fixed Drug Combination (FDC) of anti-tuberculosis therapy for 6 months. The patient gained weight, had an improvement of serum bilirubin level and had no remaining lesion in abdominal CT scan.